Use of Correlation Analysis to Examine Relationship Between Tax Burden and Business Environment in Selected EU Countries - Magdalena Brezaniova (Communications, 2013)
The aim of the article is to examine the relationship between tax burden and business environment in Slovakia, Czech Republic and Germany. The examination is carried out using correlation analysis to identify the level of dependence between selected indicators of tax burden and number of business entities in selected countries. The article contains also analysis and comparison of found facts.